Autonomy support in primary care - validation of the German version of the Health Care Climate Questionnaire - Schmidt, Konrad; Szecsenyi, Joachim (Journal of clinical epidemiology, 2011)
Objectives: There is a growing need for studies to measure how patients feel supported in their autonomy. The Health Care Climate Questionnaire (HCCQ) is an instrument to assess the physician's support to motivate the patient to take personal responsibility for his/her health. The aim of this study was to translate the HCCQ into German and validate the translated version, called the HCCQ-Deutschland (HCCQ-D). Study Design and Setting: In a cross-sectional study, we translated and culturally adapted the HCCQ, then administered the questionnaire to primary care patients from nine general practices in Germany. We used the European Task Force on Patient Evaluations of General Practice questionnaire (EUROPEP) to assess convergent validity. Subsequently, we performed Cronbach α to assess internal consistency and exploratory factor analysis to evaluate the underlying factor structure of the items. Results: Of 450 questionnaires, we included 351 (78%) in the final analysis. Internal consistency was high, with Cronbach α=0.97. We found one major underlying factor similar to the English version: all items showed a scale correlation above 0.7. The mean values of the HCCQ correlated moderately (−0.5) with those of the EUROPEP. Conclusion: This study shows similar psychometric properties of the HCCQ-D as of the original English instrument. The HCCQ-D may be appropriate to explore German-speaking patients' perceived autonomy support in primary care settings.